2018
DOI: 10.1007/s00604-018-2904-5
|View full text |Cite
|
Sign up to set email alerts
|

Tunable composites prepared from graphene oxide and zeolitic imidazolate framework-8 for improved selective isolation of hemoglobin

Abstract: The authors report on the preparation of composites made from graphene oxide (GO) and zeolitic imidazolate framework-8 (ZIF-GO), with various fractions of GO. GO acts as the template and as a modulator for the surface properties of the composites. It also improves the selective adsorption of specific proteins, i.e. hemoglobin (Hb) in this case. The adsorption capacity for Hb is as high as 436 mg g when using a composite containing 20% of GO as sorbent, and 95% of specific activity is maintained for the Hb reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…To further determine the formation and chemical structure of GZA composite, the FT-IR spectra of GO, ZIF-67, and GZA composites are shown in Figure d. For the GZA composites, the typical strong absorption bands of pure GO at 1729 cm –1 (CO) are absent, and the new peaks are displayed at 3422 and 1623 cm –1 that belong to the stretching vibrations of –OH and CC on GO. , It is reasonable to assume that the nucleation growth of Ag-ZIF-67 crystals is mainly cocontrolled by the epoxy and the carboxylic groups on the GO sheets. The data further prove the existence of the strong coordinated interaction and hydrogen bonding between GO and metal ions during the formation of GZA composites.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To further determine the formation and chemical structure of GZA composite, the FT-IR spectra of GO, ZIF-67, and GZA composites are shown in Figure d. For the GZA composites, the typical strong absorption bands of pure GO at 1729 cm –1 (CO) are absent, and the new peaks are displayed at 3422 and 1623 cm –1 that belong to the stretching vibrations of –OH and CC on GO. , It is reasonable to assume that the nucleation growth of Ag-ZIF-67 crystals is mainly cocontrolled by the epoxy and the carboxylic groups on the GO sheets. The data further prove the existence of the strong coordinated interaction and hydrogen bonding between GO and metal ions during the formation of GZA composites.…”
Section: Results and Discussionmentioning
confidence: 99%
“…21 The Fe 3 O 4 @PDA@ZIF-8 composites were employed for the extraction of low-abundance peptides and showed strong affinity, especially to those with histidine residues relying on the interaction with Zn 2+ of ZIF-8. 22 Liu et al 23 prepared ZIF-GO composites and revealed that the selectivity of this material toward hemoglobin was higher than ZIF-8. Tan et al 24 fabricated magnetic carbonized PDA@ F127/ZIF-67 hollow nanocages, which exhibited a remarkable adsorption capacity toward bovine hemoglobin up to 834.3 mg g −1 .…”
mentioning
confidence: 99%